Meaning lyrics Slank As Media Communication Social Criticism - Adydhatya Della Pahlevi; Drs. Joyo Nur Suryanto Gono, M.Si (Interaksi Online, 2016)
Music is used as a medium to convey the aspirations of social, political, and even become one of the media propaganda (information / opinions) to launch an ideological movement (idea / ideas). The lyrics is one of verbal communication media that have meaning in it. Research on the band Slank song "Gossip Streets" is a study that aims to describe the concept of the "Mafia" in the lyrics of the song and to explain the meaning of social criticism depicted. The paradigm used in this study is a critical paradigm. The theory used is the standpoint theory that provides a framework for understanding the power system. Another theory is the Critical Theory to understand the conditions that limit ratio (common sense). This research method is qualitative method in which data is interpreted (the view) through the analysis of the meaning of words written or oral form are observed. The analysis used in this research is the analysis of semiotics by Roland Barthes. Based on a study of "mafia" in the lyrics gossip streets, there is a conclusion that the mafia is described as having the properties wanted power and money have the power to set a lot of things to be achieved. In addition, the "mafia" also dare take action in the form of physical or unlawful behavior as an act of violence (hitting / slapping) and pay bribes to authorities by providing some money.